ANALISIS KEPUASAN PELANGGAN BUS DAMRI CABANGLAMPUNG - Cornelius Ary Kristiyanto; Yunada Arpan (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2020)
Perum DAMRI is a company which running in services area. In applying the objectives of the company that want to get high profits, company must provide quality services that can be accepted by customers, especially in Lampung. The formulation of problem inthis research "is there an effect of service quality towards customer satisfaction at Perum DAMRI Lampung? The purpose of this research is to prove and determine how much the effect of service quality towards customer satisfaction at Perum DAMRI Lampung both partially and totality. The population of this research or consumers who use service of DAMRI Lampung bus . While the sample of this research was 100 consumers calculated by non probability sampling using accidental sampling technique. The analysis used this research used was simple linear regression and hypothesis testing was done by t test.From the results of this research, the regression Y = 8.117 + 0.352 X indicates that the increasing of consumers quantity will increase by 0.352 if the company improves the service quality. The level of relationship between the service quality and customer satisfaction with an R value of 0.584 indicates that the level of relationship between the service quality and customer satisfaction has a strong level. The result of the effect of service quality towards customer satisfaction is 34.1%. The result of the hypothesis test indicates that there is an effect of service quality towards customer satisfaction because t count> t table (7.119> 1.66).